2005
DOI: 10.2465/jmps.100.133
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity measurement of subliquidus magmas: 1707 basalt of Fuji volcano

Abstract: We have installed a new furnace equipped with a rotational viscometer for use in viscometry at high temperature (one atmosphere) under controlled oxygen fugacities. This furnace allows sampling at the time of the viscosity measurement. Utilizing this furnace, we examined the relationship between textural parameters (crystallinity and the apparent aspect ratio of crystals) and viscosity during cooling of a basaltic magma. The 1707 basalt from Fuji volcano was used for the experiment and the result shows a drast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 22 publications
6
86
2
1
Order By: Relevance
“…With differentiation, liquid viscosity increased continuously from 45 to 302 Pa.s ( Fig. 8b; Table A4), values in good agreement with those measured on natural FeO-rich basalts (Sato 2005;Ishibashi and Sato 2007).…”
Section: Residual Liquid Versus Stratigraphic Height and Physical Prosupporting
confidence: 76%
“…With differentiation, liquid viscosity increased continuously from 45 to 302 Pa.s ( Fig. 8b; Table A4), values in good agreement with those measured on natural FeO-rich basalts (Sato 2005;Ishibashi and Sato 2007).…”
Section: Residual Liquid Versus Stratigraphic Height and Physical Prosupporting
confidence: 76%
“…Commonly accepted empirical parameter values are φ m = 0.6 and n = 2.5 (Marsh, 1981;Sato, 2005). In real magmas, however, the effect of crystallinity on magma viscosity may be several times larger than predicted by Eq.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Hence, we assume that the main mechanism responsible for the high lava viscosities (Sato, 2005). In the following section we will examine in more detail the physical conditions under which the ascent of magma and its evolution may have occurred.…”
Section: Mechanisms Behind the Observed Range Of Magma Viscositiesmentioning
confidence: 99%
“…The addition of crystals to a melt has been experimentally examined at high temperature 20 and pressure on natural or synthetic suspensions (e.g., Lejeune and Richet, 1995;Sato, 2005;Ishibashi and Sato, 2007;Lavallee et al, 2007;Caricchi et al, 2008;Cordonnier et al, 2009;Ishibashi, 2009;Picard et al, 2011;Vona et al, 2011;Picard et al, 2013). Using a variety of crystal shapes and sizes, all of the aforementioned papers showed that the abundance of crystals significantly increased the viscosity of the suspension and that aspect ratio and particle size 25 must be taken into account.…”
Section: Introductionmentioning
confidence: 99%